1993
DOI: 10.1002/1097-0142(19930901)72:5<1612::aid-cncr2820720520>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of oral ulcerative mucositis in bone marrow transplant recipients

Abstract: Background. Few longitudinal studies have investigated the onset, duration, and resolution of ulcerative mucositis in bone marrow transplant recipients. This study prospectively followed a group of such patients on a daily basis to obtain data on the incidence of ulcerative mucositis, location and duration of lesions, severity with different conditioning regimens, and the relationship of such mucositis to the absolute neutrophil count. Methods. Fifty‐nine bone marrow transplant recipients on prophylactic acycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
2
16

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 11 publications
4
116
2
16
Order By: Relevance
“…Patient-reported scores of OM severity peaked around day 5 while scores measured using the WHO, RTOG, and WCCNR scales did not peak until day 7, both of which are consistent with previous longitudinal studies of the time course of OM after HSCT. 2,4 Significantly, patients using the OMDQ often detected changes in and progression of OM severity 1-3 days earlier than clinical personnel who used the WHO scale. These results strongly suggest that the MTS components of the OMDQ may enable earlier detection of OM and may lead to changes in therapy, including earlier initiation of analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-reported scores of OM severity peaked around day 5 while scores measured using the WHO, RTOG, and WCCNR scales did not peak until day 7, both of which are consistent with previous longitudinal studies of the time course of OM after HSCT. 2,4 Significantly, patients using the OMDQ often detected changes in and progression of OM severity 1-3 days earlier than clinical personnel who used the WHO scale. These results strongly suggest that the MTS components of the OMDQ may enable earlier detection of OM and may lead to changes in therapy, including earlier initiation of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…1 Almost all patients experience some degree of OM after myeloablative therapy and BMT and approximately 75% have oral ulcers within 3-5 days after BMT. [2][3][4] OM is a result of a complex cascade of physiological events. 5 Damage from radiotherapy and chemotherapy to the rapidly dividing tissues that comprise the mucosal epithelium of the mouth and throat is followed by upregulation of transcription factors and proinflammatory cytokines in the submucosa, in turn leading to oral ulceration.…”
Section: Introductionmentioning
confidence: 99%
“…This supports previous observations that healing of OM coincides with neutrophil recovery. [20][21][22][23] Although some investigators have failed to find a link between OM and neutropenia, 5,24 Rapoport et al 25 noted that duration of neutropenia was a risk factor for OM and the severity of OM has been linked to the degree of neutropenia. 26 Oral neutrophil kinetic studies (using mouth rinses) in patients recovering from profound neutropenia have demonstrated that neutrophils are present in the tissues before peripheral neutrophil counts recover, 21,27,28 consistent with their important role in mucosal defence and repair.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of patients with oral cancer, immunosuppressed patients have an increased frequency of carriage of aerobic Gram-negative bacteria and fungi (Woo et al, 1993). The use of prophylactic antibiotics (Meissenberg et al, 1996) certainly reduces the incidence of fever and bacteraemia in this group of patients, but the impact on mucositis is less well documented.…”
Section: Antibioticsmentioning
confidence: 99%